2014
DOI: 10.1111/iwj.12329
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Grafix® for the treatment of chronic diabetic foot ulcers: results of a multi‐centre, controlled, randomised, blinded, clinical trial

Abstract: In a randomised, controlled study, we compared the efficacy of Grafix ® , a human viable wound matrix (hVWM) (N = 50), to standard wound care (n = 47) to heal diabetic foot ulcers (DFUs). The primary endpoint was the proportion of patients with complete wound closure by 12 weeks. Secondary endpoints included the time to wound closure, adverse events and wound closure in the crossover phase. The proportion of patients who achieved complete wound closure was significantly higher in patients who received Grafix (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
238
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(267 citation statements)
references
References 28 publications
17
238
3
9
Order By: Relevance
“…Scientific studies show that vCPM retain all components and properties of native fresh tissue 9. Retrospective and prospective clinical studies report positive outcomes with vCPM in management of acute and chronic wounds including complex wounds with exposed bone, tendon, or joint capsule 10, 11, 12, 13. Previously we reported vCPM use for outpatient management of two complex burn wounds that prevented potential amputation in one patient and formation of finger contracture in the second patient.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific studies show that vCPM retain all components and properties of native fresh tissue 9. Retrospective and prospective clinical studies report positive outcomes with vCPM in management of acute and chronic wounds including complex wounds with exposed bone, tendon, or joint capsule 10, 11, 12, 13. Previously we reported vCPM use for outpatient management of two complex burn wounds that prevented potential amputation in one patient and formation of finger contracture in the second patient.…”
Section: Discussionmentioning
confidence: 99%
“…et al indicó que el complejo de ácido hialurónico-fibroblastos humanos autólogos puede ofrecer un tratamiento fiable para las DFU 15 , hecho que apoya a Dermagraft por contener fibroblastos y al ácido hialuróni-co como terapia tópica que ha demostrado tendencia a la curación 11 . El producto Targeted, como productor indirecto de liberación de colágeno mostró mejoras en la cicatrización de DFU 17 , sin embargo, de las terapias investigadas en la revisión sistemática del 2015, ninguna reveló evidencia suficiente 18 11,14 . Sin embargo, la terapia con larvas (desbridamiento biológico) ha ganado peso al demostrar que acorta el tiempo de curación y aumenta la tasa de remisión total 12 .…”
Section: Discussionunclassified
“…Placental membrane also contains neonatal fibroblasts, mesenchymal stem cells (MSCs), and epithelial cells, which promote efficient wound healing (11). MSCs release soluble factors that stimulate proliferation and migration of the predominant cell types in the wound.…”
Section: Amniotic and Placental Membranesmentioning
confidence: 99%
“…Lavery et al (11) compared Grafix and SOC in treatment of DFUs, and found that 62% of Grafix patients achieved complete wound closure by week 12, compared to 21% of the SOC group (P=0.0001). Grafix patients exhibited a significantly shorter time to heal, significantly fewer adverse events (AEs), and significantly fewer wound-related infections compared with controls.…”
Section: Amniotic and Placental Membranesmentioning
confidence: 99%